Secondaryk-Kernel Symmetric Intuitionistic Fuzzy Matrices - G. Punithavalli, M. Anandhkumar (Mathematical Statistician and Engineering Applications, 2022)
The secondary k- kernel symmetric Intuitionistic fuzzy matrices are described in this studyas well as examples.Discussion is held regarding the relationships among s- k- kernel symmetric Intuitionistic fuzzy matrix, s- kernel symmetric Intuitionistic fuzzy matrix, k- kernel symmetric intuitionistic fuzzy matrix and kernel symmetric intuitionistic fuzzy matrix.For a matrix to be an Intuitionistic fuzzy matrix with an s-k kernel symmetric, necessary and sufficient conditions are established.